Measuring the Hidden Numbers of Human Trafficking Through Multiple Systems Estimation: Lessons Learned and Challenges Outstanding. (December 2021) - Durgana, Davina; van Dijk, Jan
This article takes stock of studies conducted in eight countries to estimate the prevalence of human trafficking by employing the technique of Multiple Systems Estimation on data on victims of human trafficking recorded by state and non-state institutions. It presents an overview of MSE-based prevalence estimates of human trafficking victims per 100, 000 inhabitants of these countries, disaggregated by type of exploitation, gender, and age. For some countries it also presents the different likelihoods of various sub-categories of trafficking victims, such as minors and migrant workers, to be detected by authorities and/or NGOs. Next, the article recounts what these studies have taught us about the suitability of applying MSE on existing multi-source databases to estimate the prevalence of trafficking victimization. The article concludes with a discussion on the promises and limitations of MSE and its prospects for further development, especially among developed nations.